Transformation of the enterprise risk management paradigm in Ukraine under martial law - Antoniuk, Dmytro; Kulyk, Dmytro (Management and Entrepreneurship: Trends of Development, 2026)
The article examines the transformation of the management paradigm and enterprise risk management system in Ukraine under conditions of martial law. It substantiates the declining effectiveness of traditional risk management approaches formed within a relatively stable socio-economic environment and proves the necessity of transitioning toward an adaptive managerial paradigm focused on ensuring enterprise viability and operational continuity. The study identifies key groups of risks that have gained critical importance during wartime, including security, logistics, energy, human resources, and market risks.An approach to formalizing strategic decision-making within the risk management system is proposed based on the application of integral indices of external military threat and internal resource resilience of enterprises. This approach enables the aggregation of heterogeneous risk factors and enhances the rationality and consistency of managerial decisions. Based on the combination of these indices, an algorithm for positioning enterprises within a two-dimensional “threat–resilience” space is developed, and the logic of selecting appropriate management strategies depending on index values is substantiated.An original risk management strategy selection matrix is proposed, combining the level of external military threat and internal resource resilience, which allows distinguishing four basic business behavior scenarios: hibernation, survival, relocation, and growth. The study demonstrates that applying a differentiated, indicator-oriented approach to risk management ensures alignment between threat levels, enterprise resource capabilities, and strategic managerial decisions. Overall, the integration of the proposed mechanisms into enterprise management systems contributes to mitigating the negative effects of hostilities, preserving assets, and creating prerequisites for sustainable enterprise functioning and post-war economic recovery.JEL Classification: D81, G32, L21, M21, H56.